2012
DOI: 10.1021/la300609f
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Spontaneous Motion of Condensate Drops on Superhydrophobic Copper Surfaces

Abstract: The coalescence-induced condensate drop motion on some superhydrophobic surfaces (SHSs) has attracted increasing attention because of its potential applications in sustained dropwise condensation, water collection, anti-icing, and anticorrosion. However, an investigation of the mechanism of such self-propelled motion including the factors for designing such SHSs is still limited. In this article, we fabricated a series of superhydrophobic copper surfaces with nanoribbon structures using wet chemical oxidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
142
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 156 publications
(149 citation statements)
references
References 45 publications
6
142
0
Order By: Relevance
“…First, the interspaces of the building blocks should be as small as possible, e.g., sub-micrometer scale, to avoid moisture penetration. [66][67][68][69] Second, their tip size should be as small as possible to minimize the interface adhesion. [31,50,51,[66][67][68][69] Third, the building blocks must have a certain height or depth to avoid the collapse of the suspended water bridges.…”
Section: Construction Rules Of Bionic Cmdsp Surfacesmentioning
confidence: 99%
See 4 more Smart Citations
“…First, the interspaces of the building blocks should be as small as possible, e.g., sub-micrometer scale, to avoid moisture penetration. [66][67][68][69] Second, their tip size should be as small as possible to minimize the interface adhesion. [31,50,51,[66][67][68][69] Third, the building blocks must have a certain height or depth to avoid the collapse of the suspended water bridges.…”
Section: Construction Rules Of Bionic Cmdsp Surfacesmentioning
confidence: 99%
“…[66][67][68][69] Second, their tip size should be as small as possible to minimize the interface adhesion. [31,50,51,[66][67][68][69] Third, the building blocks must have a certain height or depth to avoid the collapse of the suspended water bridges. [68] Following these design principles and inspired by nature, our group proposed and demonstrated that efficient self-propelling of small-scale condensed microdrops can be [5] Copyright 2007, Wiley-VCH.…”
Section: Construction Rules Of Bionic Cmdsp Surfacesmentioning
confidence: 99%
See 3 more Smart Citations